Последняя любовь: перевод с польского - Ожешко Элиза (Каприз. Женские любовные романы, 1993)
Экземпляры: ф.21 (2001) / Инвентарный номер: 43049 / Цена: / Сис.шифр: 84(4Пол)-4 / Авт.знак: О-45 / ГРНТИ: 17.82.30 / ББК: 84(4Пол)-446